2022
DOI: 10.3389/fpubh.2022.1021309
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood cytokines as potential diagnostic biomarkers of suicidal ideation in patients with first-episode drug-naïve major depressive disorder

Abstract: ObjectiveMajor Depressive Disorder (MDD) is a leading cause of disability, with a high risk of suicidal ideation (SI). Few studies have evaluated the potential of multiple cytokines as biomarkers for SI in patients with MDD. In the present study, we examined the serum levels of multiple cytokines in patients with first-episode drug-naïve MDD, with the aim to discover and identify serum cytokines-based biomarkers for identification of SI in MDD.MethodsA total of 55 patients with first-episode drug-naïve MDD wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Several studies found that the deficiency of omega-3 polyunsaturated fatty acids is associated with both depression symptom, neuroticism, and suicide (Conklin et al, 2007;Fujiwara & Amisaki, 2013;Pompili et al, 2017). In addition, serum albumin is also involved in the inflammatory system (Lindqvist et al, 2017), while abnormal inflammatory markers are strongly associated with suicidal ideation in depressed patients (Ekinci & Ekinci, 2017;Xu et al, 2022). Individuals with high neuroticism also show elevated levels of this inflammatory cytokine (Sutin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the deficiency of omega-3 polyunsaturated fatty acids is associated with both depression symptom, neuroticism, and suicide (Conklin et al, 2007;Fujiwara & Amisaki, 2013;Pompili et al, 2017). In addition, serum albumin is also involved in the inflammatory system (Lindqvist et al, 2017), while abnormal inflammatory markers are strongly associated with suicidal ideation in depressed patients (Ekinci & Ekinci, 2017;Xu et al, 2022). Individuals with high neuroticism also show elevated levels of this inflammatory cytokine (Sutin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some investigators had similarly attempted to construct feasible predictive models for SB in the target population of their concern. Yayun Xu and her colleagues attempted to use peripheral blood in ammatory cytokines to construct a SB model to distinguish MDD populations and found that the combination of interleukin-17C and tumor necrosis factor-beta had high accuracy (AUC = 0.848) [39]. Pu Peng and his team reported from a network perspective that the predictability of the correlation stability coe cient as the target variable is 0.53 for PSS, 0.50 for HAMA, and 0.45 for HAMD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently a study has calculated a suicide prevalence of 8.76 per 100,000 inhabitants in Mexico and previous reports have estimated 804,000 annual suicides worldwide (Cabello-Rangel et al, 2020). Major Depressive Disorder (MDD) is one of the most common mental disorders, affecting over 320 million people worldwide, and has been associated with an increased risk of suicidal ideation (SI), suicide attempts (SA), and completed suicide (Liu et al, 2022;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%